Forest ecology of India - Singh, G. B., 1944- (Jaipur : Rawat Publications, 1987)
Study of Jammu and Kashmir, India.
Includes index.
Bibliography: p. [252]-262.
Keywords: Forests and forestry -- India -- Jammu and Kashmir; Forest ecology -- India -- Jammu and Kashmir; Timber -- India -- Jammu and Kashmir; Forest products industry -- India -- Jammu and Kashmir